5(k+1)-k=3(k+2)

Simple and best practice solution for 5(k+1)-k=3(k+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(k+1)-k=3(k+2) equation:


5(k+1)-k=3(k+2)

We simplify the equation to the form, which is simple to understand
5(k+1)-k=3(k+2)

Reorder the terms in parentheses
+(+5k+5)-k=3*(k+2)

Remove unnecessary parentheses
+5k+5-k=+3+*(+k+2+)

Reorder the terms in parentheses
+5k+5-k=+(+3k+6)

Remove unnecessary parentheses
+5k+5-k=+3k+6

We move all terms containing k to the left and all other terms to the right.
+5k-1k-3k=+6-5

We simplify left and right side of the equation.
+1k=+1

We divide both sides of the equation by 1 to get k.
k=1

See similar equations:

| -6+(-9)= | | -25-6a=-4(1+6a)-3 | | 5y=12-9y | | -9(y+1)=-9 | | 4(-6)-2y=-22 | | 14+(-15)= | | Y=Z-4x | | -.25(n+5)=2 | | F(1.5)=3x-2 | | 4a+3(2a+4)=24 | | -5p+7(3p+7)=-39-6p | | 8(2n-5)=-1/2(6n-2) | | .375b+18=-2.25 | | -19+-6= | | 0.7n+5.4=-1.6 | | 3-6h=-13/6 | | 3y+1=2y+7 | | 0.7+5.4=-1.6 | | 9x^2-6x=16 | | 4x^2+14x+3=0 | | -19+(-6)= | | 0.7+5.4=-13/5 | | x^3+3x^2-5x-39=0 | | -3(k+6)=-4k-25 | | 4x+60=40 | | 6-x=12x^2 | | 3(4v+1)-3(2v+3)=2(v-7)+w | | 34+4x=-6(1+6x) | | -x+6y=-22 | | x^2=-9x-4 | | x-2(-2)=14 | | n/99=-1 |

Equations solver categories